Transcription factor 21 and prognosis in a coronary population. (3rd October 2022) - Santos, M; Mendonca, M I; Temtem, M; Sa, D; Sousa, A C; Freitas, S; Rodrigues, M; Henriques, E; Borges, S; Guerra, G; Freitas, A I; Ornelas, I; et al.
Abstract: Introduction: TCF21 is a member of the basic helix-loop-helix (bHLH) transcriptor factor family, being critical for embryogenesis of the heart. It regulates epicardium-derived cells differentiation into smooth muscle (SMC) and fibroblast lineages. The biological roles of TCF21 in epicardial fate determination and the progression of atherosclerosis remains a controversial issue. Purpose: Investigate the impact of the TCF21 rs12190287 G>C variant on the prognosis of a coronary artery disease (CAD) cohort. Methods: A prospective study was performed with 1, 713 CAD patients (mean age 53.3±7.8; 78.7% male) surveyed in terms of MACE occurrence in an extended follow-up of 5.0±4.3. TCF21 rs12190287 was genotyped and analysed using the dominant model (GC+CC) and, subsequently, compared with the wild-type GG to evaluate the survival probability by Kaplan-Meier. A Cox regression analysis with all the risk factors and genetic models was performed to assess the independent variables associated with the prognosis of CAD patients. Results: GG wild genotype was present in 9.5% of the population, GC in 43.2% and the risk genotype CC accounted for 47.3% of the CAD patients. The dominant model GC+CC showed a worse survival throughout the follow-up period. After multivariate Cox regression analysis, this model remained in the equation as an independent risk factor for MACE occurrence with an HR of 1.41 (p=0.033) together with multivessel disease, physical inactivity, chronic kidney disease (CKD) and diabetes. Conclusion: TCF21 rs12190287 is a risk factor for prognosis in our population. The role of this gene may influence fundamental SMC processes in response to vascular stress, accelerating atherosclerosis progression and may represent a target for future therapies. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): SESARAM EPERAM